2014
DOI: 10.22610/imbr.v6i6.1129
|View full text |Cite
|
Sign up to set email alerts
|

A Career Success of the Distributors in Multi-Level Marketing (MLM) Company

Abstract: Nowadays, MLM Company around the world are highly developed, and companies especially in Indonesia have been using a system of direct sales to the consumers. The career structure in MLM Company has been very much acknowledged. However, not all MLM distributors are able to achieve the line of succession. The purpose of this research is to analyse the main causes of career success in MLM Company. This study uses both quantitative and qualitative methods. The selection of samples is carried out using a snowball t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The findings of Siahaan et al (2018) supported the importance of entrepreneurship, namely entrepreneurial commitment, entrepreneurial motivation, and entrepreneurial competency, in influencing distributors' success. However, Siahaan et al (2014) found that entrepreneurial competency is partially unrelated to career success. The impact of leadership on distributors' success was further investigated in (Tsui & Lee, 2018).…”
Section: Distributor Levelmentioning
confidence: 99%
“…The findings of Siahaan et al (2018) supported the importance of entrepreneurship, namely entrepreneurial commitment, entrepreneurial motivation, and entrepreneurial competency, in influencing distributors' success. However, Siahaan et al (2014) found that entrepreneurial competency is partially unrelated to career success. The impact of leadership on distributors' success was further investigated in (Tsui & Lee, 2018).…”
Section: Distributor Levelmentioning
confidence: 99%
“…A motivated worker who runs a high level of effort will tend to believe that the level of effort will give a good rating. A good assessment will encourage the company to provide bonuses and promotions to satisfy workers' goals (Siahaan, 2014).…”
Section: Get a Bonusmentioning
confidence: 99%
“…According to the Ministry of Domestic Trade, one hundred sixty-seven companies actively and legally run MLM businesses (Kiaw & Run, 2007), they practise the pyramid system where members will find new members and gain a bonus as a profit paid in an oppressive manner (Constantin, 2009). MLM is a method of sales promotion in which a commission is paid not only to the seller responsible for making the sale but also to several levels of sellers that are responsible for distributing knowledge of the product to the seller making the current sale (Siahaan et al, 2014). MLM companies sell and promote health products, food and pharmaceutical, skincare and household products (Kiaw & Run, 2007).…”
Section: An Overview Of Multi-level Marketing Industrymentioning
confidence: 99%